Fusion Technology and Visualisation to Share STEM Data Using PETS Robots (i-COMEL) for Open Data Readiness Amongst Primary School Children - Badioze Zaman H.; Baharin H.; Ahmad A. (Springer Science and Business Media Deutschland GmbH, 2023)
Application programs; Data visualization; Engineering education; Open Data; Population statistics; Robots; Visualization; Fusion technology; Fusion technology innovation; Fusion technology strategy; Malaysia; Malaysia 5.0; Open data readiness; Open datum; STEM data; Technology innovation; Technology strategies; Students